THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE (GCG) AT PT BPRS HAJI MISKIN BASED ON OJK PRINCIPLES: LITERATURE REVIEW REVIEW - Riski Murdani; Baginda Parsaulian (Adisam Publisher, 2025)
Good Corporate Governance (GCG) is the basic framework for the creation of healthy, transparent, and integrity Islamic banking governance. In the context of BPRS, the implementation of GCG is becoming increasingly important considering the characteristics of Islamic microfinance institutions that are vulnerable to internal risks, limited human resources, and simple organizational structures. This study aims to analyze the application of GCG in PT BPRS Haji Miskin based on the five OJK principles through a literature study method. Data was obtained from scientific journals, OJK regulations, books, and previous research on BPRS governance. The results of the study show that accountability and responsibility have been carried out quite well, while transparency, independence, and internal fairness still need to be improved. This study reinforces previous findings that BPRS has distinctive governance challenges, especially related to human resources and institutional structures. This research provides a theoretical contribution to the evaluation of GCG in small-scale BPRS and offers recommendations for strengthening governance according to OJK standards.